2021
DOI: 10.1021/acs.est.1c02697
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Hydrocarbon-like Primary Organic Aerosol and Secondary Organic Aerosol Proxies Based on Their Elemental Oxygen-to-Carbon Ratio

Abstract: A large fraction of atmospheric aerosols can be characterized as primary organic aerosol (POA) and secondary organic aerosol (SOA). Knowledge of the phase behavior, that is, the number and type of phases within internal POA + SOA mixtures, is crucial to predict their effect on climate and air quality. For example, if POA and SOA form a single phase, POA will enhance the formation of SOA by providing organic mass to absorb SOA precursors. Using microscopy, we studied the phase behavior of mixtures of SOA proxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 114 publications
(218 reference statements)
3
46
0
Order By: Relevance
“…63−67 Recently, we used microscopy techniques to investigate the phase behavior of internal mixtures of hydrocarbon-like POA proxies and single-component SOA proxies. 68 We showed that two liquid phases were almost always observed when POA proxies having O/C < 0.11 were mixed with SOA proxies having 0.3 ≤ O/C ≤ 1.0. In the same study, we also found that one or two liquid phases were observed when POA proxies with 0.11 ≤ O/C ≤ 0.29 were mixed with the same SOA proxies depending on the type of the proxies.…”
Section: ■ Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…63−67 Recently, we used microscopy techniques to investigate the phase behavior of internal mixtures of hydrocarbon-like POA proxies and single-component SOA proxies. 68 We showed that two liquid phases were almost always observed when POA proxies having O/C < 0.11 were mixed with SOA proxies having 0.3 ≤ O/C ≤ 1.0. In the same study, we also found that one or two liquid phases were observed when POA proxies with 0.11 ≤ O/C ≤ 0.29 were mixed with the same SOA proxies depending on the type of the proxies.…”
Section: ■ Introductionmentioning
confidence: 73%
“…We used 11 POA proxies and examined the phase behavior of each proxy when mixed with 7 different SOA materials generated in environmental chambers, resulting in 77 unique types of internal POA + SOA mixtures studied. 68 The O/C ratios of the POA materials ranged from 0 to 0.29, covering the O/C range observed for atmospheric HOA. 20 The O/C ratios of SOA ranged from 0.37 to 1.08, covering a large fraction of the O/C range observed for atmospheric SOA (0.32−1.32).…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…25,158 Additional information about chemical speciation is necessary to determine morphology for particles with intermediate O : C values, 25,158 and these guidelines do have exceptions. 157,159,160…”
Section: Morphology Of Aerosol Particlesmentioning
confidence: 99%
“…25,158 Additional information about chemical speciation is necessary to determine morphology for particles with intermediate O : C values, 25,158 and these guidelines do have exceptions. 157,159,160 Phase separation is common for aqueous organic aerosol in the atmosphere. 158 Lee et al 161 generated nascent SSA in a wave ume using seawater from the California coast, and they found that the core-shell morphology accounted for 31.2% of all particles detected in the 100 nm to 1.8 mm size range.…”
Section: Liquid-liquid Phase Separationmentioning
confidence: 99%